The Influence of the Agreement Ratification between Ukraine and the European Union on the Labor Migration of Ukrainians - Kostiantyn NIEMETS; Kateryna KRAVCHENKO; Liudmyla NIEMETS; Kateryna SEHIDA; Oleksandr NOSYRIEV; Liudmyla KLIUCHKO (Communications of International Proceedings, 2020)
The modern world of global humanity can be described as traveling and migrating. This extremely complex modern phenomenon has many causes and factors of influence on the one hand, on the other – it affects the lives of most countries. Labor migrations are especially important. Ukraine, which until recently was on the sidelines of these processes, is increasingly participating and influencing their course, in particular, in the context of European integration. The intensification of migration processes creates a number of difficulties for both Ukraine and many EU countries, causes destabilization in the labor market, generating certain socio-demographic changes, etc. A number of documents and programs to resolve this situation in Ukraine are being developed and implemented at the state level. The authors consider the impact of ratification of the agreement with the EU on labor migration flows in Ukraine, analyze the state policy in the field of labor migration regulation, namely - the Strategy of State Migration Policy of Ukraine for the period up to 2025 in this paper.
Keywords: labor migration; illegal migration; migration flows; migration balance; population survey; Strategy of State Migration Policy of Ukraine; ratification of the association agreement.